Effect of Leadership Style and Patient Safety Culture on Awareness Patient Safety Incident Reporting with Teamwork Perception as Intervening at X Cancer Hospital Jakarta - Dharmawan, Stephen; Pamungkas, Rian Adi; Hilmy, M. Reza (Buletin Penelitian Kesehatan, 2024)
Introduction: Low patient safety incident reporting in hospitals increases adverse events, influenced by leadership style, patient safety culture, and teamwork, highlighting the importance of increased awareness. This study aims to see the effect of leadership style and patient safety culture on increasing awareness of patient safety, incident reporting, and teamwork effects as intervening variables. Methods: This type of study is quantitative research with a cross-sectional design and uses path analysis. The population in this study consisted of nurses working in inpatient and emergency departments at X Cancer Hospital Jakarta. The sampling technique used was Purposive Sampling, resulting in a total sample of 190 nurses. Data were collected using a structured questionnaire to measure leadership style, patient safety culture, teamwork, and awareness of patient safety incident reporting. Results: The results showed that patient safety culture and teamwork simultaneously affect awareness of patient safety incident reporting. Leadership style has an 8% influence, while patient safety culture has a 41.8% and 58.2% impact. Teamwork has a 47.1% and 23.6% influence, while leadership style has a 23.6% and 76.4% influence. Patient safety culture has a 36.3% and 63.7% influence, while leadership style has an 11.1% and 88.9% influence. Lastly, patient safety culture has a 17.1% and 82.9% influence, indicating that patient safety culture and teamwork are interconnected. Conclusion: The study reveals that the pasien culture and shared work significantly impact the quality of personal life.  Despite their small impact, they are crucial in creating a conducive environment for personal growth, emphasizing the importance of continuous learning and evaluation.